To compare postoperative astigmatism and visual outcome following phacoemulsification versus Manual Small Incision Cataract Surgery (MSICS) seen at tertiary care center - Priyanka; Khalid Khan; Mansi Kishnani; Mihika Dube (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
Purpose: To compare postoperative astigmatism and visual outcome following phacoemulsification versus Manual Small Incision Cataract Surgery (MSICS) seen at a tertiary care center.  Method: A total of 100 patients were enrolled in this retrospective study. Group A included 50 patients undergoing phacoemulsification surgery and group B included 50 patients undergoing MSICS. The outcome was evaluated in both techniques in terms of astigmatic profile and visual outcome at post-operative day 1 and 3 months. Results: The mean age was 60 ± 1.84 years in the phacoemulsification group and 61 ± 1.25 years in the MSICS group. In the phacoemulsification group, 60% were male patients as compared with 40% female patients while MSICS group included 62% female patients and 38 % male patients. The initial visual recovery on the first postoperative day was better in the patients who underwent phacoemulsification, with the uncorrected visual acuity better than or equal to 6/18 in 94% of the patients, whereas the percentage was 72% in the MSICS group. At three months, 80% of the patients in the MSICS group had uncorrected visual acuity better than or equal to 6/18 versus 88% of the patients in the phacoemulsification group. The mean astigmatism was 0.808 ± 0.39D in the phaco group and 1.565 ± 0.51D in the MSICS group, p-value significant (0.0001). Conclusion: Both phacoemulsification and MSICS achieved comparable and excellent visual outcomes. However, MSICS appears to be more advantageous than phacoemulsification in terms of speed, cost and independence from technology and appears to be more suitable for mass surgery especially in developing countries.